The relationship between access to debt finance and viability of small & medium enterprises in Zimbabwe - Sithole, Mupangi (Research of GSB, 2018)
The study examines the relationship between the level of access to debt finance and viability among 41 randomly selected SMEs operating in the agricultural sector in Zimbabwe for the period 2011 and 2014 using descriptive statistical analysis and panel data regression analysis. The study found that viability is positively associated with short-term debt and negatively associated with long-term debt, while it has no significant relationship with total debt. The study concludes that the level of debt accessed does not matter to viability; what matters is the type of debt accessed. It also concludes that access to debt is not the main factor associated with viability, but there are other factors such as size of business, growth opportunities, number of employees and the ratio of female to male shareholders. It is therefore recommended that SMEs managers and policy makers should be mindful of the type of debt availed to SMEs since shortterm debt is positively related to viability and long-term debt is negatively associated with viability. It is also recommended that SME managers should monitor the sizes of their enterprises and growth opportunities since these are negatively associated with viability. Female ownership of SMEs should be encouraged and supported as the results demonstrate that those enterprises dominated by female shareholders are associated with high viability. SME managers should ensure that they have adequate employees, since the results show that viability is associated increasing the number of employees.